Minimum-effort waypoint-following guidance - He, Shaoming; Lee, Changhun; Shin, Hyo-Sang; Tsourdos, Antonios (American Institute of Aeronautics and Astronautics (AIAA), 2019)
This paper addresses the problem of minimum-effortwaypoint-following guidance with/without arrival angle constraints of an Unmanned Aerial Vehicle. By utilizing a linearized kinematics model, the proposed guidance laws are derived as the solutions of a linear quadratic optimal control problem with an arbitrary number of terminal boundary constraints. Theoretical analysis reveals that both optimal proportional navigation guidance and trajectory shaping guidance are special cases of the proposed guidance laws. The key feature of the proposed algorithms lies in their generic property. For this reason, the guidance laws developed can be applied to general waypoint-following missions with an arbitrary number of waypoints and an arbitrary number of arrival angle constraints. Nonlinear numerical simulations clearly demonstrate the effectiveness of the proposed formulations.
Keywords: Aerospace; Autonomous Systems